New directions in voicing a vocation - Myers, Sally (Theology, 2019)
This article compares contemporary theological frameworks used to define 'vocation' and 'ministry' with the reported experience of those overseeing, exploring and exercising a calling to ministry within the Church of England. A comprehensive study of the recommended reading for those exploring vocation and ministry revealed the terms to be ill-defined and tending towards polarization around two viewpoints - sacerdotal priesthood rooted in the Old Testament, and presbyteral leadership rooted in the Epistles - with little theological attention being given to other perspectives, not least the ministry of Jesus as presented in the gospels. It also revealed many missing voices within the recommended reading. It found that candidates rehearsed a limited and polarized understanding of vocation and ministry, effectively learning 'BAPspeak' (a language to be used at bishops' advisory panels that recommend whether candidates should enter ministry training), but that their personal experience of vocation and subsequent ministry was much more diffuse, diverse and Jesus-shaped.